Procedural Confidentiality in Open Courts: A Theory for Managing Confidentiality Disputes in Judicial Proceedings - Vogt Geisse, Thomas Franz (2025)
This article presents a theory of procedural confidentiality, offering conceptual tools to understand and resolve disputes over confidentiality within legal proceedings. Such disputes arise when a litigant argues that unrestricted dissemination of information submitted in public judicial procedures poses a threat to a legitimate interest and requests restrictions on publicity. The legitimate interests impacted by procedural publicity (both external and internal) can be diverse – ranging from privacy and reputation to the loss of competitive advantage and professional secrets, among many others. These interests can be classified based on whether they concern risks of disclosing a secret, improper or unlawful use of the disclosed contents, or disruptions to the proper conduct of the proceedings. Each of these risks constitutes a confidentiality interest, which may be asserted as a defense (passive constellation) or as a claim (active constellation), either during the preparatory phase of information disclosure or during the evidentiary process. In each case, the court will resolve the dispute by balancing the interests of accurate fact-finding, publicity, and confidentiality, issuing an order to incorporate the information under protective conditions, with restrictions on public or party access. The appropriate measure depends on the specific risk and procedural context and may range from excluding the public from the courtroom to establishing confidentiality rings to regulate access to confidential documents.